A Technical and Conceptual Framework for Serious Role-Playing Games in the Area of Social Skill Training - Othlinghaus-Wulhorst, Julia; Hoppe, H. Ulrich (Frontiers in Computer Science, 2020)
Virtual role-playing games can provide an authentic experience of situated learning and allow for trying out different problem-solving and communication strategies without consequences in the real world. This is of particular interest and benefit for the training of social skills. This article presents a conceptual and technical framework for serious role-playing games for the training of specific social skills in virtual 2D learning environments involving chatbots in dialog-centric settings. It summarizes different use cases and evaluation results from prior studies. From the design perspective, several distinctive conceptual features characterize our framework: (1) chat-like interaction with an AI-controlled chatbot, (2) separate phases of immersion and reflection to facilitate a change of perspective that is considered conducive for learning, (3) the learning process is emphasized by means of adaptive feedback based on individual analyses. We propose a system architecture that is based on three components: (1) AI-controlled chatbots that adapt to the player's behavior, (2) a multi-agent blackboard system as the backbone in order to keep components independent and optimize performance due to parallel processing, and (3) intelligent support for an automated evaluation of the player's performance and feedback generation. The training scenarios presented and discussed in this article include workplace-oriented conflict management, patient-centered medical interviews, and customer complaint management. First evaluation studies indicate that the scenarios may be well-suited for real training situations. Due to its flexible architecture, our framework and approach can easily be tailored to different settings and use cases and thus serve as a basis for future research focusing on the adaptation to other contexts and systems. On the basis of these developments, we elaborate important design dimensions, reflect and discuss general issues and major challenges, summarize and contrast different approaches and strategies, and identify opportunities for serious role-playing games in the area of social skills training.